(untitled) (Eurasian Medical Research Periodical, 2022)
The main contingent of patients with malignant neoplasms in the Republic of Uzbekistan (in total 73,4%), who were registered in the dispensary in 2021, was formed from patients with malignant neoplasms of the kidney and accounted for 3,2%. By regions, this indicator varied from 51,6% in the Bukhara region. This review is dedicated to the topic of malignant tumors of the kidneys, to the study of prevalence and epidemiology in the Bukhara region